2021
DOI: 10.1111/lre.12353
|View full text |Cite
|
Sign up to set email alerts
|

Status, ecological services and management of aquatic weeds of floodplain wetlands in India: An overview

Abstract: Floodplain wetlands of India are biologically rich and productive ecosystems that support unique aquatic flora and fauna. Covering an area of about 0.354 million ha, the floodplain wetlands are a major source of self‐recruiting small indigenous fish (SIF). They offer vast potential for both capture and culture‐based fisheries, securing livelihood and nutrition for a large section of the population. In addition to tremendous anthropogenic pressures and climatic variability, these resources have experienced a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…However, an infestation of aquatic macrophytes in Indian oodplain wetlands is causing severe ecological and economic issues. Degradation and shrinkage of wetlands have been seen during the last several decades as a result of the development of aquatic weed infestation, necessitating immediate attention to their conservation and restoration to confront their oncoming di culties (Sarkar et al 2021). In the present investigation, it has been found that both the wetland has moderate to high visible macrophyte coverage (Table 4).…”
Section: Assessment Of Macrophytementioning
confidence: 99%
“…However, an infestation of aquatic macrophytes in Indian oodplain wetlands is causing severe ecological and economic issues. Degradation and shrinkage of wetlands have been seen during the last several decades as a result of the development of aquatic weed infestation, necessitating immediate attention to their conservation and restoration to confront their oncoming di culties (Sarkar et al 2021). In the present investigation, it has been found that both the wetland has moderate to high visible macrophyte coverage (Table 4).…”
Section: Assessment Of Macrophytementioning
confidence: 99%
“…Inland fishing resources include 1.96 lakh kilometers of rivers and canals, 3.15 million hectares of reservoirs, 2.44 million hectares of lakes and ponds, 0.798 million hectares of derelict water bodies, 1.24 million hectares of brackish water regions and 0.29 million hectares of estuaries. While the wetlands in the country's floodplains comprises about 500,000 hectares, providing a significant amount of territory for the development of culture-based fisheries (Sarkar et al 2021). With 7.58 percent of global fish output, India ranks second in the globe.…”
Section: Major Source Of Indian Fisheriesmentioning
confidence: 99%
“…Some studies have shown significant differences in the decomposition products of different plants ( Zhao et al., 2017 ). By managing the reaping of aquatic plants, the re-release of substances into the water environment can be avoided to a certain extent, which may stabilize the quality of the water environment ( Sarkar et al., 2021 ). However, the disposal of the material after a plant has been reaped has become a new problem.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the disposal of plants litter, incineration of this plant litter ( Tong et al., 2018 ), as well as resource utilization, including their use as fodder, herbs, biomass, energy and other positive uses were observed ( Sarkar et al., 2021 ). Some studies have focused on the use of plants litter as a carbon source, which may improve the nitrogen removal efficiency in constructed wetlands during the treatment process of low-carbon and, high-nitrogen incoming water ( Wu et al., 2018 ; Zhao et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%